Laser micro adjustment - From new basic process knowledge to the application - Schmidt, Michael; Dirscherl, Manfred; Rank, Matthias; Zimmermann, Maik (Journal of Laser Applications, 2007)
Laser micro bending and its controlled variant, laser micro adjustment, have been known for many years. Different theories on the working principle, mainly differing in interaction time and energy flux density, have been evolved and experimentally proven. The temperature gradient mechanism and the buckling mechanism are the most established laser adjustment techniques. However, as interaction times are getting shorter with the development of new laser sources, additional phenomena are being detected and new interaction principles have to be investigated. In this paper the use of the thermal upsetting mechanism for adjusting fiber optical components will be demonstrated. An actuator for micro positioning of optical fibers relative to collimating optics is designed using numerical simulations and experimental results. The benefit of laser adjustable actuators in building an automated, modular production line will then be presented by introducing a system developed for the assembly of fiber optical components. As heat impact and thermally induced damaged are becoming a serious issue for laser adjustment in micro technology, new nonthermal adjustment mechanisms using ultrashort laser pulses are experimentally demonstrated and their interaction principles derived. Thus this contribution will both give the latest scientific information on the latest theories concerning novel laser forming mechanisms and focus on examples for the migration of well established process variants into industrial use. © 2007 Laser Institute of America.
Created from Fastlane, Scopus look-up
Keywords: Actuators; Adjustment; Fiber alignment; Laser; Micro bending